1198. Lyme Disease Post-Exposure Prophylaxis by Single-Dose Doxycycline in Three Healthcare Systems. (4th December 2021) - Marx, Grace E; Schotthoefer, Anna M; Schwartz, Brian S; Draper, Evan; Rivera, Christina G; Zeuli, John; Scotty, Erica; Pollak, Jonathan S; Schwartz, Amy M; Beck, Alyssa; Hinckley, Alison F
Abstract: Background: Lyme disease, the most common tickborne disease in the United States, may be prevented by taking a single 200-mg dose of oral doxycycline after a high-risk bite from a blacklegged tick. Currently, it is not known how Lyme disease post-exposure prophylaxis (PEP) might vary by region and healthcare system. We identified single-dose doxycycline medication orders in three healthcare systems in states with high incidence of Lyme disease and compared associated patient and provider characteristics. Methods: Electronic health record data during 2012 – 2016 were obtained from three healthcare systems: Geisinger (Pennsylvania), Marshfield Clinic (Wisconsin), and Mayo Clinic (Minnesota/Wisconsin). Creation of analytic variables and analysis were harmonized across the three sites. Medication orders for single-dose doxycycline ≤200 mg that were accompanied by specific key words or diagnostic codes (e.g., tick bite; Lyme disease prevention) were considered evidence of PEP. Manual chart review was performed from a random subset to evaluate the algorithms used to identify PEP. Results: Among 2, 937, 585 patients with at least one medication order or clinical encounter during the study period, 14, 102 single-dose doxycycline orders for Lyme disease PEP for 13, 172 unique patients were identified. The typical patient receiving PEP was older (mean age 51 – 58 years), male (56 – 59%), and non-Hispanic White (81 – 98%). The annual seasonality of medication orders was bimodal, with peaks occurring during April – July and October – November. The most common encounter setting was an outpatient clinic or urgent care center (80 – 91%); medication orders after patient phone calls in the absence of an in-person visit occurred frequently (14 – 19%) in two health systems. Chart abstractions (n=600) revealed instances of PEP prescribed inappropriately (e.g., bite from a non-blacklegged tick; patient with symptoms of acute Lyme disease). Conclusion: Lyme disease PEP with a single dose of doxycycline was frequently prescribed in healthcare systems where there is a high incidence of Lyme disease. PEP was most commonly prescribed to non-Hispanic Whites over the age of 50 years. Public health initiatives for tickborne disease prevention should include clinician education on the appropriate use of Lyme disease PEP. Disclosures: Anna M. Schotthoefer, PhD, HelixBind (Other Financial or Material Support, salary support) John Zeuli, PharmD, INSMED (Other Financial or Material Support, honoraria for educational speaking)